Anion-templated nanosized silver clusters protected by mixed thiolate and diphosphine. Issue 10 (1st March 2017) - Li, Xiao-Yu; Wang, Zhi; Su, Hai-Feng; Feng, Sheng; Kurmoo, Mohamedally; Tung, Chen-Ho; Sun, Di; Zheng, Lan-Sun
Abstract : Anion template effects were exemplified in six novel high-nuclearity silver clusters constructed using mixed S- and P-donor ligands. Abstract : S 2−, MoO4 2−, and Mo6 O22 8− were successfully employed as templates in the formation of six high-symmetry polynuclear silver clusters as exemplified in the single-crystal X-ray structures of [S@Ag18 ( t BuC6 H4 S)16 (dppp)4 ]·DMF·5CH3 CN·3CH3 OH (1 ), [MoO4 @Ag24 (MeC6 H4 S)12 (dppm)6 (MoO4 )4 ]·2BF4 ·C2 H5 NO (2 ), [MoO4 @Ag24 (MeC6 H4 S)12 (dppm)6 (MoO4 )4 ]·2CF3 SO3 (3 ), [MoO4 @Ag24 (MeC6 H4 S)12 (dppf)6 (MoO4 )4 ]·2CF3 SO3 (4 ), [MoO4 @Ag24 (MeC6 H4 S)12 (dppb)6 (MoO4 )4 ]·2CF3 SO3 (5 ) and [Mo6 O22 @Ag46 ( t BuC6 H4 S)32 (dppm)4 (CH3 CN)8 ]·6CF3 SO3 (6 ) (dppp = 1, 3-bis(diphenylphosphino)propane, dppm = bis(diphenylphosphino)methane, dppf = 1, 1′-bis(diphenylphosphino)ferrocene and dppb = 1, 4-bis(diphenylphosphino)butane). Cluster1 is a S 2− -centered octadecanuclear banana-shaped molecule. Clusters2–5 have similar structures consisting of a tetrahedron of a MoO4 2− core and four MoO4 2− where three silver atoms cap each face and a pair sits on each edge, giving tetraicosanuclear ball-shaped molecules. Although different diphosphine ligands and silver salts were used in the syntheses, 2–5 contain a common building cluster unit with similar geometry and nuclearity. With (Bu4 N)2 Mo6 O19 as a template, a giant 46-silver-atom cluster encapsulates an in situ modified Mo6 O22 8− unit. The nuclearity and geometry depend on the size and shape of the templates. High-resolution electrospray mass spectrometry (HR-ESI-MS) analyses of4 indicate its exceptionally high stability in acetonitrile. The solid-state luminescence of1 as a function of the temperature exhibits thermochromism from red to yellow due to the different intensities of the two bands. This work established a new strategy for the construction of polynuclear silver clusters using an anionic template and mixed S- and P-donor ligands where a promising approach for building novel dual emissive materials is unraveled.